ChemInform Abstract: Dehydrogenative Lactonization of Diols in Aqueous Media Catalyzed by a Water‐Soluble Iridium Complex Bearing a Functional Bipyridine Ligand. Issue 30 (29th July 2014) - Fujita, Ken‐ichi; Ito, Wataru; Yamaguchi, Ryohei
Abstract The novel protocol allows the conversion of various benzylic and aliphatic diols into the corresponding lactones in aqueous media in the presence of a water soluble and reusable iridium catalyst.